The Works of Samuel Johnson, in Sixteen Volumes. Volume 04 - Johnson, Samuel, 1709-1784 (Salt Lake City, UT : Project Gutenberg, 1996)
"The Works of Samuel Johnson, in Sixteen Volumes. Volume 04" by Samuel Johnson is a collection of essays and reflections written in the early to mid-18th century. This volume includes various pieces from "The Rambler," where Johnson addresses themes of morality, human conduct, and societal issues through engaging narratives and character studies. The essays aim to provoke thought about human nature, social norms, and the struggles of individuals contending with their circumstances. At the start of the volume, the opening essay features a character named Misella, who recounts her harrowing experiences as a young woman who succumbs to a life of prostitution. In her narrative, she reflects on her journeys through guilt and despair, highlighting the harsh realities faced by women in society and how desperation can lead to moral degradation. This poignant account sets the tone for the essays to come, which delve into topics such as the corrupting nature of sudden wealth, the complexities of criticism, and the challenges of maintaining virtue in a flawed world. Overall, the beginning of the work lays a foundation for Johnson's exploration of philosophical and ethical dilemmas faced by individuals in varying social contexts. (This is an automatically generated summary.)
Release date is 1996-07-01
Scanned by Charles Keller with OmniPage Professional OCR software donated by Caere Corporation
Keywords: Essays